Discovery and development of orexin receptor antagonists as therapeutics for insomnia - Winrow, C J; Renger, J J (British journal of pharmacology, 2014)
Insomnia persistently affects the quality and quantity of sleep. Currently approved treatments for insomnia primarily target γ‐aminobutyric acid‐A (GABA‐A) receptor signalling and include benzodiazepines and GABA‐A receptor modulators. These drugs are used to address this sleep disorder, but have the potential for side effects such as tolerance and dependence, making them less attractive as maintenance therapy. Forward and reverse genetic approaches in animals have implicated orexin signalling (also referred to as hypocretin signalling) in the control of vigilance and sleep/wake states. Screening for orexin receptor antagonists using in vitro and in vivo methods in animals has identified compounds that block one or other of the orexin receptors (single or dual orexin receptor antagonists [SORAs and DORAs], respectively) in animals and humans. SORAs have primarily been used as probes to further elucidate the roles of the individual orexin receptors, while a number of DORAs have progressed to clinical development as pharmaceutical candidates for insomnia. The DORA almorexant demonstrated significant improvements in a number of clinically relevant sleep parameters in animal models and in patients with insomnia but its development was halted. SB‐649868 and suvorexant have demonstrated efficacy and tolerability in Phase II and III trials respectively. Furthermore, suvorexant is currently under review by the Food and Drug Administration for the treatment of insomnia. Based on the publication of recent non‐clinical and clinical data, orexin receptor antagonists potentially represent a targeted, effective and well‐tolerated new class of medications for insomnia. Linked Articles This article is part of a themed section on Orexin Receptors. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2014.171.issue‐2